Model keberkesanan pengurusan fasiliti perumahan bertingkat bukan kos rendah di Malaysia / Adi Irfan Che Ani - Adi Irfan, Che Ani (2007)
Living in high-rise residential schemes becomes a trend for Malaysians as the ownership for landed property is more and more expensive to be owned. In line with that, the buyer/owner is more concerned about the quality of living environment, not just merely buying the parcel unit of the house. This makes the aspect of housing management should be put at a fore front with the careful planning as well as effective management. In achieving this target, the concept of facility management is then synchronized with the aspect of high-rise residential management. This research gives focus to the non low-cost high-rise residential scheme only, as relatively the facilities provided for this particular scheme is more as compared with the low-cost housing schemes. As for the sample, the total of 150 housing schemes are taken, in which the council member of Management Corporation is fully by the residents. This criterion is set to be so as the Management Corporation run by the residents is the permanent one as long as the strata title is not being terminated. The foremost aim of the research is to develop the model of effective facility management that form as instrument and gives beneficial to the Management Corporation in measuring their effectiveness performance. Other than that, the current scenario of facility management in non low-cost high-rise residential is also discussed throughout the research work. The primary method in developing the effectiveness model is by quantitative paradigm, with the use of Path Analysis and administrate by the software of Analysis Moment of Structures (AMOS). Other than AMOS, the software of Statistical Package for Social Sciences (SPSS) is adopted for analysing the descriptive and inferential statistics. The main findings of the research is regarding the developed research constructs, namely financial, maintenance and resident, which is found as significant factors in developing the effectiveness model. Apart from this, three research dimensions have to be withdrawn from being part of the effectiveness model, namely service quality, residents involvement and residents responsibility. This because these three dimensions is found not significant via the path analysis. As for the current scenario, it reveals that the facility management in non low-cost high-rise residential schemes in Malaysia is at the level of neutral only.Furthermore, there is an understanding gap identified between the Council Member of Management Corporation and residents of housing schemes. The gap is concerned about the satisfaction level in all situations of facility management, in which the satisfaction of Council Member of Management Corporation is slightly higher that residents. The research generalization is limited to the Management Corporation operated by the residents only in non low-cost high-rise residential schemes.The aspect of location and category of housing schemes, be it condominium, apartment, town house or mixed development, can be put aside in generalizing the research findings since there is no significant difference in measuring the effectiveness variable. This in turn led to delimitation of generalization to those non low-cost high-rise residential schemes that is subjected under the Strata Title Act 1985, regardless of the location of one particular housing scheme.